Frozen Rice Consumption Reduces Blood Glucose Response: Glycemic Index and Glycemic Load Analysis - Purbowati; Septiani; Sri Siska Mardiana (Media Gizi Indonesia, 2026)
Rice is a staple food for most Indonesians. Freezing rice for 24 hours and then reheating it will lower glucose levels and increase resistant starch (RS), thus affecting the glycemic index (GI) and glycemic load (GL). This quantitative study used a crossover design, with subjects acting as both the control and intervention groups. The GL and GL analysis involved 10 healthy respondents, aged 19-29 years with normal nutritional status and fasting blood glucose levels. The data were normally distributed, so an independent sample T-test was used to examine the differences in GL and GL between rice and frozen rice. The results of the analysis of carbohydrate, glucose, and RS content in rice were rice (34.01%, 43.57%, 20.06%), frozen rice (25.94%, 39.62%, 23.59%), and rice (25.94%, 39.62%, and 23.59%), respectively. There was a significant difference in GI between regular rice (82.61) and frozen rice (76.41) p-value 0.005 (>0.05), as well as a significant difference (p-value 0.001 (<0.05)) between BG of regular rice (28.1) and frozen rice (19.82). It was concluded that rice and frozen rice differed in the rate of increase in blood glucose per gram of carbohydrate and in the total impact on blood glucose levels.